Decomposition of abnormal free locomotor behavior in a rat model of Parkinson's disease - Grieb, Benjamin; Von Nicolai, Constantin; Engler, Gerhard; Sharott, Andrew; Papageorgiou, Ismini; Hamel, Wolfgang; Engel, Andreas K.; Moll, Christian K. (Frontiers in Systems Neuroscience, 2013)
Poverty of spontaneous movement, slowed execution and reduced amplitudes of movement (akinesia, brady- and hypokinesia) are cardinal motor manifestations of Parkinson´s disease that can be modeled in experimental animals by brain lesions affecting midbrain dopaminergic neurons. Most behavioral investigations in experimental parkinsonism have employed short-term observation windows to assess motor impairments. We postulated that an analysis of longer-term free exploratory behavior could provide further insights into the complex fine structure of altered locomotor activity in parkinsonian animals. To this end, we video-monitored 23 hours of free locomotor behavior and extracted several behavioral measures before and after the expression of a severe parkinsonian phenotype following bilateral 6-hydroxydopamine (6-OHDA) lesions of the rat dopaminergic substantia nigra. Unbiased stereological cell counting verified the degree of midbrain tyrosine hydroxylase-positive cell loss in the substantia nigra and ventral tegmental area. In line with previous reports, overall covered distance and maximal motion speed of lesioned animals were found to be significantly reduced compared to controls. Before lesion surgery, exploratory rat behavior exhibited a bimodal distribution of maximal speed values obtained for single movement episodes, corresponding to a ‘first’ and ‘second gear’ of motion. 6-OHDA injections significantly reduced the incidence of second gear motion episodes and also resulted in an abnormal prolongation of these fast motion events. Likewise, the spatial spread of such episodes was increased in 6-OHDA rats. The increase in curvature of motion tracks was increased in both lesioned and control animals. We conclude that the discrimination of distinct modes of motion by statistical decomposition of longer-term spontaneous locomotion provides useful insights into the fine structure of fluctuating motor functions in a rat analogue of Parkinson´s disease.